(untitled) (Research, Society and Development, 2023)
The article aims to analyze social inequality in Brazil, given the pertinence of goal 10.4 of the 2030 Agenda, which aims to reduce social inequality, verifying whether the reduction could generate losses and/or limitations in social relations, in the face of the economy and public policies. Through a qualitative approach, documental and bibliographical research and analysis of official secondary data. Starting from the analysis of the goals and action plans of the United Nations (UN) and through the GINI Index, one of the main indicators used to estimate the inequalities of a society, demonstrating the parameters used for comparison and what are the effects and impacts that the new objectives of the UN can generate in society. From a different perspective, in a debate scenario, with a close eye on government public policies that generate social causes, taking into account the prioritization of searches on public policies and fiscal and salary areas and how the government could contribute to the reduction of inequality in Brazil.